2014
DOI: 10.1038/ejhg.2013.311
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome due to a missense mutation

Abstract: Fragile X syndrome is a common inherited form of intellectual disability and autism spectrum disorder. Most patients exhibit a massive CGG-repeat expansion mutation in the FMR1 gene that silences the locus. In over two decades since the discovery of FMR1, only a single missense mutation (p.(Ile304Asn)) has been reported as causing fragile X syndrome. Here we describe a 16-year-old male presenting with fragile X syndrome but without the repeat expansion mutation. Rather, we find a missense mutation, c.797G4A, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 25 publications
0
106
0
Order By: Relevance
“…To determine if R138Q-FMRP can bind mRNA, we infected Fmr1 KO cortical neurons with R138Q-FMRP or WT-FMRP lentivirus and performed FMRP-RNA coimmunoprecipitation (co-IP) to measure the relative mRNA levels of three validated FMRP targets: Map1b, Dlg4, and CamKIIα (1). We found that R138Q-FMRP associated with these targets to a similar level as WT-FMRP, whereas neurons infected with the functional null G266E-FMRP mutant (26), or GFP alone, did not pull down these mRNAs and were significantly different from WT-FMRP as expected ( Fig. 2B; two-way ANOVA with a significant main effect of lentivirus infection; F = 66.57, P < 0.0001, Dunnett's post hoc analysis: *P < 0.0001 for pairwise comparison with WT-FMRP control group for each mRNA target).…”
Section: R138q Mutation Retains Postsynaptic Functions Of Fmrp In Tramentioning
confidence: 70%
See 2 more Smart Citations
“…To determine if R138Q-FMRP can bind mRNA, we infected Fmr1 KO cortical neurons with R138Q-FMRP or WT-FMRP lentivirus and performed FMRP-RNA coimmunoprecipitation (co-IP) to measure the relative mRNA levels of three validated FMRP targets: Map1b, Dlg4, and CamKIIα (1). We found that R138Q-FMRP associated with these targets to a similar level as WT-FMRP, whereas neurons infected with the functional null G266E-FMRP mutant (26), or GFP alone, did not pull down these mRNAs and were significantly different from WT-FMRP as expected ( Fig. 2B; two-way ANOVA with a significant main effect of lentivirus infection; F = 66.57, P < 0.0001, Dunnett's post hoc analysis: *P < 0.0001 for pairwise comparison with WT-FMRP control group for each mRNA target).…”
Section: R138q Mutation Retains Postsynaptic Functions Of Fmrp In Tramentioning
confidence: 70%
“…Both of these mutations reside within the RNA binding domains of FMRP and result in loss of RNA binding and polyribosome association (26,28). Studies of these mutations provide strong evidence that FMRP's inability to regulate protein synthesis is a critical component of FXS pathophysiology, given that both of the patients with the G266E and I304N mutations presented with a very characteristic FXS phenotype, including marked ID, developmental delay, macroorchidism, and dysmorphic facies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragile X Mental Retardation Protein (FMRP) is among the most important RBPs because of its central role in several human diseases (3). Loss of FMRP function due to CGG triplet repeat expansion-associated transcriptional silencing or missense mutations in the protein (4,5) lead to fragile X syndrome (FXS), the most common cause of inherited intellectual disability. Mutations in FMRP are also the leading monogenic cause of autism (6,7).…”
mentioning
confidence: 99%
“…Despite significant analysis of the FMR1 gene, only a small number of conventional genetic mutations, such as point mutations and insertions/deletions, have been reported to be associated with FXS or developmental delay (20)(21)(22)(23)(24)(25)(26)(27). To identify causes of developmental delay attributable to FMR1 variants other than the repeat expansion, our group sequenced the FMR1 gene in 963 developmentally delayed males, each of whom tested negative for the CGG expansion mutation, and discovered a number of previously unreported variants (28).…”
mentioning
confidence: 99%